Is Lung Disease a Risk Factor for Sudden Cardiac Death? A Comparative Case–Control Histopathological Study - Ioana Radu; Anca Otilia Farcas; Septimiu Voidazan; Carmen Corina Radu; Klara Brinzaniuc (Diseases)
Background/Objectives: Sudden cardiac death (SCD) constitutes approximately 50% of cardiovascular mortality. Numerous studies have established an interrelation and a strong association between SCD and pulmonary diseases, such as chronic obstructive pulmonary disease (COPD). The aim of this study is to examine the presence of more pronounced cardiopulmonary histopathological changes in individuals who died from SCD compared to the histopathological changes in those who died from violent deaths, in two groups with comparable demographic characteristics, age and sex. Methods: This retrospective case–control study investigated the histopathological changes in cardiac and pulmonary tissues in two cohorts, each comprising 40 cases of SCD and 40 cases of violent death (self-inflicted hanging). Forensic autopsies were conducted at the Maramureș County Forensic Medicine Service, Romania, between 2019 and 2020. Results: The mean ages recorded were 43.88 years (SD 5.49) for the SCD cohort and 41.98 years (SD 8.55) for the control cohort. In the SCD cases, pulmonary parenchyma exhibited inflammatory infiltrate in 57.5% (23), fibrosis in 62.5% (25), blood extravasation in 45% (18), and vascular media thickening in 37.5% (15), compared to the control cohort, where these parameters were extremely low. In myocardial tissue, fibrosis was identified in 47.5% (19) and subendocardial adipose tissue in 22.5% (9) of the control cohort. Conclusions: A close association exists between SCD and the histopathological alterations observed in the pulmonary parenchyma, including inflammation, fibrosis, emphysema, blood extravasation, stasis, intimal lesions, and vascular media thickening in intraparenchymal vessels. Both the histopathological modifications in the pulmonary parenchyma and vessels, as well as those in myocardial tissue, were associated with an increased risk of SCD, ranging from 2.17 times (presence of intimal lesions) to 58.50 times (presence of interstitial and perivascular inflammatory infiltrate in myocardial tissue).